Analisis Anomali Kebijakan Penempatan TKI: Eksploitasi Tenaga Kerja Indonesia sebagai Anak Buah Kapal Perikanan Taiwan - Hafriz Resa Damarsidi; Hermini Susiatiningsih; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
This research aims to explain why Indonesian Government keep assigning Indonesian workers into Taiwan fisheries ship. Qualitative research with the explanative method is used to explain the correlation between variables. Range of this research is between 2013 and 2016. Interview and literature review used as data collection technique. This research use public policy theory, human rights concept, foreign policy concept, and rational choice theory as analytical tool. The result obtained from this research is there are a reason that benefit the state and society based on domestic and external factors, as well as the social, political, defense and security impacts. So as rationally based on consideration of profit and loss The Government of Indonesia has a reason to keep the Indonesian Workers Placement Policy at Taiwan Fisheries Ship Crew.